HEMATOPOIETIC CELL TRANSPLANTATION FOR JUVENILE MYELOMONOCYTIC LEUKEMIA AND OTHER MYELOPROLIFERATIVE NEOPLASMS - Villela, Neysimelia Costa; Oliveira, Anita Frisanco; Ferreira, Rafaela de Souza; Zamperlini, Gustavo; Bassani, Andréia Cristina Fortes; Michalowski, Mariana Bohns; Lee, Maria Lúcia de Martino (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2025)
Juvenile myelomonocytic leukemia (JMML) is a rare and distinctive hematologic neoplasm affecting infants and younger children. Hyperactivation of the RAS signaling pathway is a central initiating event in JMML, which also delineates its various genetic and clinical subtypes. While a small percentage of children may achieve spontaneous clinical remission, allogeneic hematopoietic cell transplantation (HCT) remains the only possible cure for most JMML patients. In this article, we reviewed the indications of HCT in JMML. Other myeloproliferative diseases, such as polycythemia vera, essential thrombocythemia, and primary myelofibrosis, are extremely rare in pediatrics and are briefly discussed.